Serious Gaming in Medical Education: A Proposed Structured Framework for Game Development. Issue 4 (August 2017) - Olszewski, Aleksandra E.; Wolbrink, Traci A.
Abstract : Summary Statement: Serious games are increasingly being used for medical education. However, the design and development of serious games for the education of health professionals is highly variable, and very few articles report the development process used for game development. There are many established processes for software development that can improve and streamline development, and incorporating the best practices from educational pedagogy and software development may enhance teamwork and communication, decrease development costs, and improve the quality of serious games. In this article, we review and summarize the literature for serious game development for medical education, and combining the best practices, we propose a structured three-phase iterative development framework for serious game development.